Les referències culturals en la traducció indirecta: Gràcies per la propina de Ferran Torrent en alemany. - Robles, Ferran; Benavent, Sabina (Zeitschrift für Katalanistik, 2025)
This work has a double purpose: on the one hand, it studies the use of culturemes in the novel Gràcies per la propina (1994) by Ferran Torrent; on the other hand, it analyses their translation into German, carried out indirectly through the Spanish version. The results obtained show the importance of these units in the construction of a realistic narrative, which recreates the environments and material culture of the time in which the plot takes place, and of a discourse that brings the reader closer to Valencian popular speech. As for the transfer of culturemes, the research shows that a general strategy aimed at preserving cultural specificities is followed throughout the work. It becomes manifest in the frequent choice of exoticising translation techniques. However, certain types of culturemes are transferred preferably through domesticating techniques: especially in the case of linguistic culturemes, an effort has been made to maintain the colloquial and popular character of discourse, to the detriment of the cultural component.